√(4x + 91) - √(11x + 1) - √(7x + 4) = 0
одз 4x + 91 > =0 x> =-91/4
11x + 1> =0 x> =-1/11
7x+4> =0 x> =-4/7
x > =-1/11
√(4x + 91) - √(7x + 4) = √(11x + 1) возводим в квадрат
4x + 91 - 2√(4x + 91)√(7x + 4) + 7x + 4 = 11x + 1
11x + 95 - 2√(4x + 91)√(7x + 4) - 11x - 1 = 0
√(4x + 91)√(7x + 4) = 47
(4x + 91)(7x + 4) = 47²
28x² + 16x + 637x + 364 - 2209 = 0
28x² + 653x - 1845 = 0
d = 426409 + 206640 = 633049 (≈796²)
x₁₂ = (-653 +- √633049)/56
x1 = (-653 - √633049)/56 < -1/11 не корень
x2=(-653 + √633049)/56
ответ:
объяснение:
1) условие читается по-разному:
1 вариант:
2/3 х = 1
2/3 × х = 1
х = 1: 2/3 = 1 * 3/2 = 3/2
х = 1 1/2
х=1,5
2 вариант:
2/3х =1
2 : 3х = 1
3х = 2: 1
3х= 2
х = 2/3
2)
5х = 1/6
х= 1/6 : 5 = 1/6 : 5/1 = 1/6 * 1/5
х = 1/30
3)
4х=1/4
х= 1/4 : 4 = 1/4 * 1/4
х = 1/16
4)
7х=20
х= 20 : 7 = 20/7
х= 2 6/7
Поделитесь своими знаниями, ответьте на вопрос:
Выражение а) 5ху * ( -0, 2 ху) б) 8абс * ( -3аб)